Evaluasi KPI Terhadap Maturitas BLU: Studi Kasus Poltekkes Pontianak dan Poltekkes Surakarta - Rybob Khomes; Atik Nurwahyuni (POLTEKKES KEMENKES YOGYAKARTA, 2025)
This study aims to evaluate the indicators on the KPI towards the maturity level of the Public Service Agency (BLU), especially the financial and service aspects at the Poltekkes Kemenkes Pontianak and Poltekkes Kemenkes Surakarta. This study is a continuation of the author's previous research entitled